Effects of obliquity and water vapor/trace gas greenhouses in the early martian climate. Issue 3 (31st March 2013) - Mischna, Michael A.; Baker, Victor; Milliken, Ralph; Richardson, Mark; Lee, Christopher
Abstract: [1] We explore possible mechanisms for the generation of warm, wet climates on early Mars as a result of greenhouse warming by both water vapor and periodic volcanic trace emissions. The presence of both water vapor (a strong greenhouse gas) and other trace greenhouse gases (such as SO2 ) in a predominantly CO2 atmosphere may act, under certain conditions, to elevate surface temperatures above the freezing point of liquid water, at least episodically. Variations in obliquity are explored to investigate whether these periodic variations in insolation at Mars can broaden the regions or seasons where warm temperatures can exist. We use the Mars Weather Research and Forecasting general circulation model to perform several simulations of the conditions of the early martian atmosphere containing these gases and find global temperatures to be cooler than the elevated levels suggested by at least one recent study by Johnson et al . (2008). While achieving temperatures above 273 K globally remains challenging, the additional warming by greenhouse gases under certain obliquity states can permit for widespread seasonally warm conditions, which can help to explain the presence of fluvial surface features (e.g., valley networks) and hydrous minerals of post‐Noachian age, a period when alternate methods do not convincingly explain the sustainability of liquid water. Furthermore, we find that global warming can be achieved with the presence of a darker surface globally, which is consistent with both widespread exposure of unweathered basaltic bedrock or the presence of a large surface ocean or sea. Key Points: Obliquity state and volcanic gases together enhance greenhouse warming. Periodic greenhouse events in Mars history explain observed fluvial features. Dark surfaces, consistent with liquid water, enhance surface warming